Becoming a reflective educator: A case study at UiTM Pahang / Sulaila Bakar, Allina Nadzri and Azlini Razali - Bakar, Sulaila; Nadzri, Allina; Razali, Azlini (2009)
The concept "reflective thought" was first introduced by John Dewey in 1933 in his book How We Think; a book designed for teachers. Little did he know, almost a century later, his basic assumption that 'learning improves to the degree that it arises out of the process of reflection' is still being discussed by scholars around the world. As time goes on, the term 'reflection' spreads, producing a host of synonyms, such as 'critical thinking', problem solving' and 'higher level thought '. Reflective teaching is viewed as the path forward for both learners and educators alike and it leads to better learning and teaching. This study sets out to identify who among the lecturers in UiTM Pahang are ready in the pursuit of becoming reflective educators.